Embracing chatbots as learning agent: a scoping literature review - Rosmalily Salleh,; Vaikunthan Rajaratnam,; Abtar Darshan Singh,; Abu Yazid Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the era of digital education, the demand for personalised and adaptive learning tools has grown significantly. AI-powered chatbots have emerged as innovative solutions, offering learners tailored guidance and real-time feedback. This paper introduces the Personalised Constructivist Agent Model (PCAM), a theoretical framework that integrates principles from constructivism, adaptive learning theories, and self-determination theory. The PCAM demonstrates how chatbots can enhance personalised learning, foster active knowledge construction, and promote intrinsic motivation by synthesising established educational theories. Through a comprehensive review of theoretical underpinnings and practical applications, this study highlights the transformative potential of chatbots in education. It also addresses key implementation challenges, including ethical considerations, cultural sensitivity, and the balance between automation and human interaction. The findings offer valuable insights for educators, researchers, and developers seeking to harness the capabilities of chatbots to create engaging, effective, and inclusive educational experiences.